THE STRATEGY OF STUDYING THREE-LIQUID PHASE EQUILIBRIA IN THE CONCENTRATION SPACE OF QUATERNARY MIXTURES - A. Yu. Sebyakin; A. K. Frolkova (Тонкие химические технологии)
When separating multicomponent heterogeneous mixtures in units consisting of a distillation column and a decanter, a fundamental question is the location of phase separation regions with different numbers of liquid phases in the concentration simplex. A solution of this issue is based on data on the vapor-liquid and liquid-liquid equilibria of the mixture and its components, as well as on the general laws of the formation of the topological structure of phase separation areas. A strategy of studying the three-liquid phase equilibrium area in quaternary mixtures is proposed. The strategy is based on the formula of a topological invariant of the separation region and on the mathematical concept of centroid - the intersection point of three medians. The presence of threeliquid phase areas of separation of open and closed types is shown. They differ in the absence (presence) of region of degeneracy via the critical node.